The moderating effect of supervisor support on the relationship between flexible working arrangements, work-family conflict and employee performance - Eni Suriana Alias (2022)
This study aimed to examine the moderating effect of supervisor support (SS) on the relationship between flexible working arrangements (FWAs), work-family conflict (WFC) and employee performance (EP). This study primarily focused on the organizations that adopted flexible working arrangement (FWA). The selected organizations were obtained from the report by TalentCorp Malaysia FWAs in collaboration with Malaysian Employer Federation (MEF). The questionnaires were distributed to 304 employees of the selected organizations through Human Resource Department. The sample was selected using the purposive sampling technique. The data were analysed using Binary Logistic Regression. This study found that there was a significant negative effect of work interference with family (WIF) (B = 2.672, p =.015) and family interference with work (FIW) (B = 3.425, p =.022) on job quality performance (JQP); and WIF (B =1.868, p =.034) and FIW (B = 2.001, p =.041) on task performance (TP). The findings also showed the significant and negative effect of FWAs on JQP (B = -3.495, p =.045) and TP (B = -3.686, p =.001). The findings showed supervisor support (SS) as significant moderator in the relationship between FIW-JQP (B = - .793, p =.042), and FWAs-TP (B = 1.045, p =.001). In conclusion, FWAs and WFC are significant predictors of EP which the relationship is in a negative direction. SS only served as a significant moderator in the relationship between FWAs-TP; and FIW-JQP. In implications, to enhance employee performance, the managers of the organization need to encourage the family supportive supervisors culture; flexible working arrangements and work-family conflict.